How information presentation formats influence usage behaviour of course management systems: flow diagram navigation versus menu navigation. Issue 2 (25th January 2022) - Tang, Pengfei; Yao, Zhong; Luan, Jing; Xiao, Jie
ABSTRACT: Educational informatisation (e.g. e-learning, m-learning, massive open online courses (MOOCs)) has actively increased, leading to a greater focus on the design and development of course management systems. In this study, a research model based on cognitive fit theory and scanpath theory is proposed to investigate how information presentation formats (flow diagram navigation versus menu navigation) of a course management system influence user experience and intention. Performance load (cognitive load and kinematic load) and user perception (perceived usefulness and ease of use) are considered to evaluate user experience. The results of an eye tracking experiment utilised in this research reveal the following. First, information presentation formats can significantly influence user experience of course management systems. Second, flow diagram navigation fits students' tasks better and leads to lower performance load and better use perception. Third, performance load and user perception shows a significant effect on user satisfaction and thereby affect the intention. These findings deepen our understanding of the importance of information presentation and enrich its theoretical foundation for course management systems development. Practically, these findings provide designers with guidelines on how to improve user experience and increase use intention by varying information presentation formats.